Mugil hospes Jordan & Culver in Jordan 1895 - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Mugil hospes Jordan & Culver, 1895. Hospe Mullet . To 30 cm (11.8 in) TL (Robertson and Allen 2002). Atlantic and Pacific sides of Americas (Robertson and Allen 2002); just inside Punta Pequena (26°14’N, 112°27’W), southern Baja California (Personal communication: Los Angeles County Museum of Natural History Fish Collection, Los Angeles, California), and Gulf of California to Ecuador (Robertson and Allen 2002). Depth: 0 to 10 m (33 ft) Robertson and Allen 2002). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 92, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008